(untitled) (Research, Society and Development, 2022)
Introduction: The medical clinic proves its importance in medicine when it encompasses content from various medical specialties, being a prerequisite for most of them. Objective: This work aims to analyze and compare the perception of medicine students about Internal Medicine, through the application of 2 questionnaires. Method: This is a quantitative, observational, descriptive and cross-sectional study, with the application of two questionnaires, one of which is the The Dundee Ready Education Environment Measure (DREEM) and the other elaborated by the authors on a Likert scale, comparing the students’ perception about of the various subspecialties of clinical medicine in the pre- and post-internship period, evaluating the degree of importance and difficulty for learning. Both were applied to eighth and twelfth semester students at Centro Universitário Christus (Unichristus). The analysis of the exposed data will be essential for a better teaching planning for students, being a great benefit in the academic sphere. Results: Questionnaires were applied to 147 students, 79 (53.7%) from the 8th semester and 68 (46.2%) from the 12th semester. There was a predominance of females (61.2%), resulting in 90 students. By observing the DREEM questionnaire, obtained by the average score of all participants, it allowed the identification of strengths, such as the positive perception of students about the tutors, and weaknesses, such as the perception of learning. The total score average was 132.76, meaning “More Positive than Negative”. Conclusion: With the results obtained, it was possible to analyze the educational environment at Centro Universitário Christus, in addition to comparing the perception of pre-boarding and post-boarding students about some medical specialties, noting that the educational environment in the institution’s medical clinic is considered good by the students.